Improving magnetic and structural properties of Zn1–xCuxFeCrO4 by substituting copper synthesized by citrate gel autocombustion route. (March 2015) - Hankare, P.P.; Tapase, A.S.; Pandav, R.S.; Garadkar, K.M.; Mulla, I.S.
Abstract: The nanocrystalline Zn1− x Cu x FeCrO4 ( x =0.0, 0.25, 0.50, 0.75 and 1.0) have been synthesized by citrate-gel autocombustion method. X-ray diffraction (XRD) confirmed formation of cubic spinel structure for all the compositions. The lattice constant ( a ) shows a decreasing trend with the increase in Cu content. Thermal analysis of precursor after autocombustion was carried out by using thermo gravimetric analysis (TG–DTA). Formation of spherical nanoparticles was revealed by transmission electron microscopy (TEM). The elemental analysis by SEM–EDAX was in close agreement with the expected composition of the starting composition used for the synthesis. The room temperature magnetic properties studied by using the vibrating sample magnetometer (VSM) indicate ferrimagnetic nature of the samples. The role of copper in the formation of modified structural and magnetic properties of these samples has been explained.